2015
DOI: 10.1088/1751-8113/48/22/225302
|View full text |Cite
|
Sign up to set email alerts
|

Qubit state transfer via discrete-time quantum walks

Abstract: Abstract. We propose a scheme for perfect transfer of an unknown qubit state via the discrete-time quantum walk on a line or a circle. For this purpose, we introduce an additional coin operator which is applied at the end of the walk. This operator does not depend on the state to be transferred. We show that perfect state transfer over an arbitrary distance can be achieved only if the walk is driven by an identity or a flip coin operator. Other biased coin operators and Hadamard coin allow perfect state transf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 45 publications
0
45
0
Order By: Relevance
“…By discrete-time quantum walk search algorithm, M. Stefaňàk et al discussed state transfer on star graphs and complete bipartite graphs [24]. Yalcinkaya et al [25] designed qubit state transfer with discrete-time quantum walk on a N -circle and N -line by adding some recovery operator to the whole system. However, for the N -circle protocol, N should be even number, and the transferred state can only be transmitted to the opposite site on the circle.…”
Section: Introductionmentioning
confidence: 99%
“…By discrete-time quantum walk search algorithm, M. Stefaňàk et al discussed state transfer on star graphs and complete bipartite graphs [24]. Yalcinkaya et al [25] designed qubit state transfer with discrete-time quantum walk on a N -circle and N -line by adding some recovery operator to the whole system. However, for the N -circle protocol, N should be even number, and the transferred state can only be transmitted to the opposite site on the circle.…”
Section: Introductionmentioning
confidence: 99%
“…A state transfer is required in such quantum algorithms. It is, however, difficult to control the state transfer because the quantum walk is inherently random [5,9,16,17]. One of the propositions to solve this problem is a coin that has a part in determining the movement of the quantum walk.…”
Section: Introductionmentioning
confidence: 99%
“…Barr et al [6] investigated discrete quantum walks on variants of cycles, and found some families such as K 2 + C n that admit perfect state transfer with appropriately chosen coins and initial states. In [34], Yalcnkaya and Gedik proposed a scheme to achieve perfect state transfer on paths and cycles using a recovery operator. With various setting of coin flippings, Zhan et al [36] also showed that an arbitrary unknown two-qubit state can be perfectly transfered in one-dimensional or two-dimensional lattices.…”
Section: Introductionmentioning
confidence: 99%